Gamma-tocotrienol alters protein expression of HepG2 cell line - Farahani ARS,; Zakiah J,; Abdul Rahman M,; Karsani SA,; Wan Ngah WZ, (Penerbit UKM, 2008)
Gamma-tocotrienol (GTT) has been shown to exhibit significant antitumor activity in a variety of tumor cells. Previous findings have demonstrated that GTT had antiprolifera-tive effects on a liver cancer cell line (HepG2) with an IC50 value of 170μM. In this study, two dimensional gel electrophoresis (2DE) was used to determine changes in protein expression in HepG2 cell line following treatment with GTT. The ultimate aim is to identify the possible molecular mechanisms involved in GTT antitumor activity. This study is focused on obtaining a 2DE protein profile for HepG2 cell line with and without GTT treatment. In the preliminary analysis of the resulting 2DE profiles, 18 protein spots were found to be differentially expressed in cells treated with GTT. This observa-tion is confirmed by extending the analysis to a larger sample size. By studying the effects of GTT treatment on differential protein expression in HepG2 cells the underly-ing mechanisms involved in the antitumor activity of GTT may be elucidated